JavaScript DOM projects for interactive dynamic Webpages (Packt Publishing, 2022)
Explore how you can create amazing mini projects to learn JavaScript - grow your portfolio - expand your skills! About This Video Get started with JavaScript DOM coding and development Create fun interactive games and components with JavaScript Learn to detect collision between page elements with JavaScript DOM In Detail JavaScript can bring your web pages to life. Select page elements, make changes and update them as needed. Power up your web pages. Create amazing content on your pages, driven dynamically with JavaScript. Projects within this course are designed to help you learn more about JavaScript and interacting with the DOM. Learn by example, this course is loaded with fun projects to help you learn and prove what can be done with JavaScript. First is an introduction to the DOM and how JavaScript can create page interactions. Explore how to write JavaScript code, select page elements, and more. This course is loaded with useful projects to help you learn more about creating interactive and dynamic web content with JavaScript. The course covers the following topics: JavaScript projects DOM interactive Dynamic webpages Introduction to web development Course resource guide JavaScript starter projects DOM simple projects to start coding JavaScript DOM interactive components and useful projects JavaScript DOM fun projects Interactive DOM elements By the end of the course, you will be able to create interactive and dynamic web content with JavaScript. Who this book is for This course is for JavaScript developers, web designers, web application developers, web masters, and for anyone who wants to create fun web projects and someone who wants to learn more about JavaScript and the DOM. Beginner JavaScript knowledge is needed as the course covers only JavaScript relevant to the building of the game. Also, HTML and CSS knowledge is essential as the scope of this course is all focused-on JavaScript.